A BRIEF ANALYSIS OF THE PROSECUTOR'S INVESTIGATIVE POWER OF THE INTERNATIONAL CRIMINAL COURT (World Bulletin of Management and Law, 2024)
In order to punish international crimes and ensure justice and justice in the international community, the establishment of domestic criminal justice systems has been unable to cope with cross-regional international crimes. The call for justice and peace led to the establishment of a long-term international criminal justice institution. Therefore, the International Criminal Court came into being. Therefore, the International Criminal Court came into being. The Court established the Office of the Prosecutor to receive and examine referred situations and any factual information about crimes within the jurisdiction of the Court, to investigate and prosecute in the Court. The Office of the Prosecutor has the power to investigate and prosecute crimes of genocide, crimes against humanity, aggression and war crimes committed by citizens of States parties or committed within the territory of States parties. At present, the international community has high hopes for the International Criminal Court, and the impartial exercise of the Prosecutor's powers is crucial for the ICC to sanction international crimes and operate effectively. Therefore, further research on the powers of the Prosecutor of the International Criminal Court is needed, and some clear suggestions for improvement need to be made to eliminate these difficulties.